2008
DOI: 10.1007/s10562-008-9727-7
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Oxides-Containing Titanium Silicalite for Liquid Phase Epoxidation of 1-octene with Aqueous Hydrogen Peroxide

Abstract: Tungsten oxides (WO 3 ) have been supported on the titanium silicalite (TS-1) by impregnation method. The solids have been tested for epoxidation of 1-octene with aqueous H 2 O 2 in acetone as solvent. It was found that the presence of tungstate species in the catalysts enhanced the rate of the formation of epoxide. Diol as a site-product was also observed due to the acidic properties of the catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…The absorption bands at around 1100, 800 and 450/cm were lattice modes associated with internal linkages in [SiO 4 ] tetrahedral [29]. The absorption bands at around 1230 and 547/cm were characteristic peaks of the MFI type zeolite structure [30], which were consistent with the XRD characteristic MFI structure. The vibrational modes at around 970/cm are commonly believed to be the stretching mode of the [SiO 4 ] tetrahedral bond with Ti atoms and the fingerprint of framework titanium [31][32][33][34].…”
Section: Ft-ir Spectrasupporting
confidence: 63%
“…The absorption bands at around 1100, 800 and 450/cm were lattice modes associated with internal linkages in [SiO 4 ] tetrahedral [29]. The absorption bands at around 1230 and 547/cm were characteristic peaks of the MFI type zeolite structure [30], which were consistent with the XRD characteristic MFI structure. The vibrational modes at around 970/cm are commonly believed to be the stretching mode of the [SiO 4 ] tetrahedral bond with Ti atoms and the fingerprint of framework titanium [31][32][33][34].…”
Section: Ft-ir Spectrasupporting
confidence: 63%
“…Prasetyoko et al 161 studied the performances of WO 3 supported on the titanium silicates (TS-1) by impregnation method for epoxidation of 1-octene in H 2 O 2 and acetone medium at 70 °C. All samples show good activity (WO 3 /TS-1: 930 h −1 ).…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…Since a group at Enichem rst reported the synthesis of TS-1 zeolite in 1983, 1 many researchers have tried to understand the properties of this microporous catalyst. [2][3][4][5] TS-1 zeolite is a redox molecular sieve with a MFI structure which is usually used in the selective oxidation of various organic compounds with hydrogen peroxide as oxidant under mild conditions, such as the epoxidation of olens, [6][7][8][9] the hydroxylation of aromatic compounds, [10][11][12][13] the ammoximation of ketones, 14,15 and the oxidation of alkanes, alcohols and sulfur-containing compounds. [16][17][18][19][20][21] It is indicated that TS-1 is capable of catalyzing the hydroxylation reaction of aromatics in the presence of hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%